Recent Discoveries in Arran - Mann, Ludovic McLellan (Proceedings of the Society of Antiquaries of Scotland, 1925)
A round cairn with passage, central chamber, and ring of stones was excavated near Carmahome. The central circular chamber was well-constructed with flooring and walls formed of vertically set slabs. The chamber sat within a circle of originally ten uprights, all covered by the cairn. A flint knife was found below one of the floor slabs. Three fragments of bronze axe-heads of the flanged or early palstave type were found at Pirnmill during building work. The axe-heads are very similar, yet were made in different moulds. The little hoard was probably left by an itinerant founder; it was not a merchant's stock or a personal hoard. The axes were old before they were deposited in the ground, as they have anciently been broken up into convenient fragments, perhaps for the crucible.